Tillage Study for Corn and Soybeans: Comparing Vertical, Deep, and No-Tillage - E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2021)
Trends from a tillage study conducted since 2011 have shown no clear differences between tillage systems for either corn or soybeans in lighter soils under irrigation. One year out of eight years has shown a yield advantage for either corn or soybeans for any tillage system, which appears to be related to environmental conditions experienced during the season. Averaged across all years of the study, the treatments with deep tillage either every or every-other year had about 3.5% higher corn yields, and soybeans had up to a 2.9% yield increase with some form of tillage.
Keywords: tillage; corn; soybeans; vertical tillage; no-tillage